WEB Oriented Constructivist Learning to Increase Students’ Self Regulation and Academic Achievement - Iis sumiati; Neneng Windayanib; Wati Susilawati; Rahayu Kariadinatad (CV. Generasi Intelektual Digital (GEN ID), 2024)
Constructivist learning emphasizes the active role of learners in constructing knowledge through experience, social interaction, and reflection. However, students often encounter difficulties in meeting the prerequisite knowledge required for effective learning. This study aims to examine the effect of web oriented constructivist learning on improving students' self regulation skills and academic achievement in Biology, particularly in biodiversity topics. The research employed an experimental method with a One Group Pretest-Posttest Design involving 38 students from class X-MIA 6 at a senior high school in Bandung Regency. Data were collected using questionnaires and test instruments, then analyzed through gain calculation and multiple linear regression. The results indicated a moderate increase in both self regulation skills and academic achievement based on the gain index. Furthermore, the correlation analysis revealed that the constructivist approach and self regulation skills collectively had a significant positive impact on students' academic achievement. These findings suggest that integrating a web oriented constructivist approach can effectively enhance self regulation skills and learning outcomes in Biology education.